Nutritional composition of potato (Solanum tuberosum L.) Haulms - Kaplan, Mahmut; Ulger, Ismail; Kokten, Kagan; Uzun, Sati; Oral, Elif Varhan; Ozaktan, Hamdi; Temizgul, Ridvan; Kale, Hasan (Progress in Nutrition, 2018)
The present study was conducted to investigate the nutritional composition of the haulms of commonly grown 5 potato (Solanum tuberosum L.) cultivars (Milva, Laura, Granola, Europrima and Jelly). Plant materials were harvested from potato production fields of Efsane Seed Company just before tuber harvest. Current findings revealed that green herbage yields of potato haulms varied between 416.51 and 670.32 kg/da, dry herbage yields between 381.62 and 527.24 kg/da, crude protein (CP) ratios between 10.85-14.48%, crude ash (CA) ratios between 5.22 and 9.10%, acid detergent fiber (ADF) ratios between 22.46 and 33.94%, neutral detergent fiber (NDF) ratios between 47.99 and 60.91%. Gas production values varied between 33.15 and 47.56 mL, methane productions between 5.27 and 8.35 mL, metabolic energy (ME) values between 7.45 and 9.29 MJ/kg DM and organic matter digestibility (OMD) values between 50.77-63.69%. Considering the mineral content of potato haulms, iron contents varied between 47.35 and 180.07, manganese contents between 28.14 and 85.15, cobalt contents between 0.43 and 1.13, nickel contents between 3.40 and 8.60, copper contents between 10.84 and 15.35, zinc contents between 4.14 and 15.60, cadmium contents between 1.02 and 1.55 and lead contents between 6.74 and 9.80 mg/kg/DM. It was concluded based on current findings from the haulms of five different potato cultivars that haulms had quite high feed quality values. With rich mineral contents, haulms may eliminate supplementary mineral requirements of livestock. Therefore, it can be stated that haulms of all five cultivars can be used as an alternative feed source for animals.